CORRELATION BETWEEN HEALTHCARE SERVICE QUALITY AND HIV TESTING SERVICES PATIENT’S SATISFACTION IN KEDUNGDORO PRIMARY HEALTH CARE SURABAYA - Arinda Agung Katritama; Pudji Lestari; Muhammad Vitanata Arifijanto (Current Internal Medicine Research and Practice Surabaya Journal, 2022)
Introduction: Service quality of primary healthcare centre especially at HIV testing services must be improved. When the service quality is improved there will be a positive feedback such as patient’s satisfaction. Within the high patient satisfaction rate, People Living with HIV (PLWH) are expected to be more active, productive and also invited friends to check themselves, so the iceberg phenomenon will be revealed and prevention will be easier to control.Methods: This research used observational analytic design with purposive sampling method. The total research sample was 189  respondent, assess the questionnaire that consisted of five dimensions of service quality which were tangible, reliability, responsiveness, empathy and assurance, and also three indicators of patient satisfaction which were overall satisfaction, expectation and experience.Results: Among 189 respondents, mostly male with 129 responses or 68.3%, according to age group, mostly from 20-25 years old age group with 88 responses or 46.6% and according to time visit, mostly first visit patient with 162 responses or 85.8%. According to service quality, mostly categorized in a good group with 173 respondents or 91.5%. In patient satisfaction, mostly were categorized in a satisfy group with 157 respondents or 81.5%, There was a positive correlation between service quality and patient satisfaction with p value <0.01 and correlation coefficient 0.632.Conclusion: There is a correlation between every dimension of service quality which are tangible, reliability, responsiveness, empathy and assurance with patient satisfaction of HIV testing services patient in Kedungdoro Primary Health Care Surabaya